Program Kesehatan Jiwa Berbasis Gampong Melalui Kolaborasi Mahasiswa dan Kader Kejiwaan dalam Upaya Meningkatkan Partisipasi dan Kepercayaan Diri Penyandang Disabilitas di Gampong Lampaya - desi maharani, fifi (Jurnal Riset dan Pengabdian Masyarakat, 2026)
Persons with disabilities, particularly those with mental disabilities, continue to face limited social participation and low self-confidence due to stigma and the lack of inclusive activity spaces at the community level. The gampong (village), as the social structure closest to the community, plays a strategic role in supporting community-based mental health initiatives. This article aims to describe the implementation of a Gampong-Based Mental Health Program in enhancing the participation and self-confidence of persons with disabilities in Gampong Lampaya, Lhoknga District, Aceh Besar Regency. This study employed a descriptive qualitative approach, with data sources obtained through observation, interviews with mental health cadres, assessments and home visits of persons with disabilities, as well as activity documentation. The results indicate that the gampong-based mental health program, implemented through collaboration between KPM students and mental health cadres, was able to increase the participation of persons with disabilities not only in terms of attendance but also through active involvement and more open social interaction. In addition, the program contributed to strengthening the self-confidence of persons with disabilities through inclusive and supportive activity approaches. These findings affirm that a gampong-based mental health approach has strong potential as a relevant social empowerment strategy for improving the psychosocial functioning of persons with disabilities at the community level.